Dissolution test of herbal medicines containing Paullinia cupana: validation of methods for quantification and assessment of dissolution - Sandra Alves de Sousa; Henrique Pascoa; Edemilson Cardoso da Conceição; Suzana Ferreira Alves; Danielle Guimarães Almeida Diniz; José Realino de Paula; Maria Teresa Freitas Bara (Universidade de São Paulo, 2011)
"Guaraná" (Paullinia cupana) is used as a physical activity enhancer and stimulator due to its methylxanthines and condensed tannins. The aim of this work was to evaluate the dissolution behavior of five herbal medicines in the form of capsules and tablets containing guaraná. Assay and dissolution methods were validated and results obtained allowed simultaneous marker quantification with precision, accuracy, selectivity and robustness. Findings showed that 100% of the herbal medicinal products analyzed did not provide satisfactory results concerning the presence of four markers, 60% had three markers (caffeine, catechin and epicatechin), while 40% had only caffeine at tested dosage forms. In addition, after 30 minutes, only capsule A showed at least 80% of the dissolved markers. In other capsules, marker dissolution did not exceed 60% whereas 60% of the samples had some characteristic pharmacotechnical problems. These results evidence the need for rigorous quality control to help ensure the therapeutic action of these drugs. To this end, dissolution studies are an essential tool for quality assurance of herbal medicines. Guaraná (Paullinia cupana) é utilizado como revigorante e estimulante devido à presença de metilxantinas e taninos condensados. Este trabalho visou avaliar o comportamento de dissolução de cinco fitoterápicos, na forma de cápsulas e comprimidos, contendo guaraná. O método de quantificação e de dissolução foram validados e os resultados obtidos permitiram a quantificação dos marcadores simultaneamente, com precisão, exatidão, seletividade e robustez. Foi verificado que 100% dos fitoterápicos analisados encontravam em desacordo quanto à presença dos quatro marcadores, sendo que 60% apresentaram três marcadores (cafeína, catequina e epicatequina) e 40% apresentaram somente a cafeína. Além disso, após o tempo de 30 minutos de ensaio foi possível observar que somente a cápsula A apresentou pelo menos 80% dos marcadores dissolvidos. Nas demais cápsulas o comportamento de dissolução apresentado pelos marcadores não ultrapassou 60% e, além disso, 60% das amostras apresentaram alguns problemas farmacotécnicos característicos. Frente aos resultados obtidos torna-se evidente a necessidade de um rigoroso controle de qualidade que contribua para assegurar a ação terapêutica desses medicamentos e, nesse sentido, o estudo de dissolução constitui uma ferramenta essencial para a garantia de qualidade dos fitoterápicos.